Targeted screening in the UK: A narrow concept with broad application - Anna Bobrowska; Molly Murton; Farah Seedat; Cristina Visintin; Anne Mackie; Robert Steele; John Marshall (Elsevier, 2022)
Summary: A recent report on screening in the UK proposed that the responsibility for recommendations on population and targeted screening programmes should be held by one new integrated advisory body. There is no wide international consensus on the definition of targeted screening. Our review identified and compared the defining components of screening terms: targeted, population, selective, and cascade screening, and case finding. Definitions of targeted screening and population screening were clearly demarcated by the eligible population; targeted and selective screening were found to be conceptually interchangeable; cascade screening, whilst conceptually similar to targeted screening across several components, was only used within the context of genetic diseases. There was little consensus between different definitions of case finding. These comparisons contributed to an updated definition of targeted screening. Considerable overlap between definition components across terms implies that a broad range of disease areas may fall into the remit of the new advisory body.